Symmetrically multi-connected optical fiber wide area networks. - Liu, Feng. (University of Ottawa (Canada), 1994)
Self-routing all-optical WAN design is becoming more and more important in broadband communications. However, little has been done in this field. In this thesis, we propose a Multi-Dual Ring Connected Shuffle Network and a Multi-Shuffle Connected Shuffle Network for a WAN environment. The performance of the proposed architectures is studied under a uniform traffic pattern analytically and numerical results are provided. The Multi-Dual Ring Connected Shuffle Connected Networks are studied under the nonuniform traffic patterns with an analytical method 'extreme value analysis' and a simulation method 'random load generation'. All of the studies are done with respect to the Perfect Shuffle Networks. The proposed architectures outperform the conventional Perfect Shuffle Network proposed in the literature.
Keywords: Engineering, Electronics and Electrical.